GutMicrobiotAware: an international exploratory survey on awareness and understanding of the gut microbiota - Garcia-Gutierrez, Enriqueta; Arbulu, Sara; Oliver, Charlotte; Kumar, Sandeep; Dam, Sarita A.; Jakobi, Babette; Pennone, Vincenzo; Sarda, Fabiana A. Hoffmann; Mukherjee, Arghya; Cotter, Paul D. (Frontiers in Microbiology, 2026)
Over the past two decades, scientific understanding of the composition and function of the human gut microbiome has expanded substantially. The recent surge in human gut microbiota-related studies has unveiled the profound influence of the gut microbiota on host nutrition, health, and behavior, bridging biology, medicine, and ecology, among others. The dynamic interaction between daily lifestyle choices, life events, and the gut microbiota makes it understandably, a topic of interest among the lay public. Communicating scientific insights from the laboratory to the population effectively, however, can be challenging, and might involve adapting the delivery of knowledge to different audiences, using precise language in corresponding settings and the use of more accessible concepts in public forums such as science festivals or social media. With the growing interest in gut microbiota beyond academic circles, there is also an increased risk of disseminating information lacking scientific rigor. The current study aimed to assess the general knowledge regarding the gut microbiota among an exploratory pool of participants, primarily accessed via academic and social networks, and evaluate healthcare professionals’ understanding of its links to various health conditions, ultimately informing better communication strategies for both groups. Our findings from this exploratory survey indicate that while most participants were familiar with the gut microbiota, instances of partial and even complete misconceptions persisted. The results from our survey further underlined the need for targeted scientific communication to emphasize the microbial diversity of the gut microbiota, the factors influencing it, its links to health conditions, and the realistic scope of current microbiota analyses.